The Deconstruction of “Metanarrative” of Traditional Detective Fiction in Martin Amis’s Night Train: A Postmodern Reading - Güneş, Ali (Journal of History Culture and Art Research, 2018)
This paper examines this view of “unreliable” or “little narrative” or “incredulity toward metanarrative” in Martin Amis’s novel Night Train as an anti-detective novel. In so doing, the paper falls into two parts. The first part focuses upon the convention of traditional “reliable” or “metanarrative” in a typical traditional detective story, in which Mike Hoolihan as a detective investigates Jennifer Faulkner’s suicide by collecting all the possible evidences and then examining them in a chronological linear way to solve her enigmatic death: who has killed her? Why was she murdered? If it is suicide, why has she ended her life? However, the paper also discusses that the way Mike passionately attempts to solve Jennifer’s mysterious death is not possible due not only to lack of evidences but also to the fact that there occurs various interpretations about her death, including Mike’s her one, which, after a while, turns into a psychological evaluation of the case with her own emotional involvement. Hence Jennifer’s death remains a mystery from the beginning to the end in the novel. This situation obviously defies the expectation of her father Tom as in the traditional sense because why Tom hires Mike as an “exceptional interrogator” with an outstanding “paperwork” in the past is to clarify the case and then appease his anxiety, as well as the mystery of his daughter’s death. Through his representation of Mike in such a condition, Amis apparently illuminates that it is almost impossible to create a detective story with a final legitimate total meaning and resolution as in a typical traditional detective novel in an age based on fragmentation, uncertainty, doubt, interruption, lack of authority, and self-expression.